Exploring dynamic capabilities, intellectual capital and innovation performance relationship: Evidence from the garment manufacturing - Wendra Wendra; Ernie Tisnawati Sule; Joeliaty Joeliaty; Yudi Azis (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
The notions of dynamic capabilities, intellectual capital, and innovation performance have been examined in many competitive advantage scholarly papers. However, there have been small numbers of management studies that consider the link of dynamic capabilities and intellectual capital in respect of innovation performance. Previous studies tend to argue that dynamic capabilities played a mediator or moderator role on intellectual capital and innovation performance linkage. Therefore, this study seeks to propose a new perspective that dynamic capabilities are the antecedents of intellectual capital leading to innovation performance. Thus, the rationale for this study is to propose a conceptual model and to provide empirical support on the mediator role of intellectual capital in dynamic capabilities and innovation performance linkage. By using accidental and snowballs sampling techniques, this study distributed questionnaires to 297 small and medium enterprises of the garment manufacturing in Indonesia. Partial least square offers the main statistics methodology for data analysis. Results show that dynamic capabilities had a significant influence on intellectual capital and innovation performance. Moreover, intellectual capital partially mediated dynamic capabilities' influence on innovation performance. Therefore, it is expected that organisations should grow, implement and maintain their dynamic capabilities in order to improve their intellectual capital and innovation outcomes. Lastly, some future studies are suggested.
Keywords: M10; M12; O31; O34; 650; competitive advantage; dynamic capabilities; garment manufacturing; innovation performance; intellectual capital; partial least square; small and medium enterprises